Assessment of the effect of bone density on implant stability: A clinical study - Raghunadh Sreerama; Krishna Chaitanya Kolluru; Vineela Gottumukkala; Chaitanya Kumar Innampudi; Jagga Rao Konathala; G Krishnaveni (Wolters Kluwer Medknow Publications, 2021)
Background: In this study, we determined the effect of bone density on implant stability. Methodology: Two hundred and sixty dental implant sites in 128 patients were assessed for resonance frequency analysis (RFA) following implant insertion, at 6 months and 12 months. The implant stability quotient (ISQ) was determined. Results: The mean ± standard deviation bone density in anterior mandible was 862.8 ± 203.4 Hounsfield units (HU), in posterior mandible was 528.4 ± 115.6 HU, in anterior maxilla was 594.2 ± 95.2 HU, and in posterior maxilla was 438.1 ± 110.2 HU. The mean insertion torque in successful implants was 38.2 ± 7.1 Ncm and in failed implants was 22.4 ± 4.2 Ncm. The mean RFA value in successful implants was 65.4 ± 5.8 and in failed implants was 45.8 ± 4.1 ISQ. A statistically significant (P < 0.05) difference was obtained. Conclusion: Within the limitation of the study, we observed that successful implants exhibited higher RFA and insertion torque and were higher into failed implants suggesting a correlation of bone quality and implant stability parameters.